Bathymetry of the Aleutian Arc, United States-Alaska / U.S. Department of Commerce, Environmental Science Services Administration, Coast and Geodetic Survey - U.S. Coast and Geodetic Survey (1967)
Title in lower left corner: Bathymetric map Relief shown by contours and spot heights. Depths shown by soundings, isolines, and bathymetric tints "Transverse Mercator projection." "This edition prepared and printed from ESSA monograph no. 3." Includes sheet index and "Sounding density diagram." Sheets numbered 1910N-2, 1910N-1, 1810N-2, 1810N-1, 1710N-2, 1710N-1 Sheets numbered in lower right margin: A-5254 to A-5259 Attu --Kiska--Adak--Amlia --Unalaska--Unimak Color 1:400,000